Contemporary implications of the first-century counter-ethos of Jesus to the scripted universe of gender and health in John 4 & 9 : a narrative-critical analysis - De Milander, Cornelia (Stellenbosch : Stellenbosch University, 2015)
Thesis (MTh)--Stellenbosch University, 2015.